The Effect of Environmental Pollution Game-Based Learning on Improving Students' Conceptual Understanding and Environmental Awareness - Arif Widiyatmoko; Muhamad Taufiq; Aji Purwinarko; Indah Urwatin Wusqo; Melissa Salma Darmawan (Journal of Innovation in Educational and Cultural Research, 2022)
The purpose of this study is to analyze the effect of "Environmental Pollution Game-Based Learning (EPGBL)" on improving students’ conceptual understanding and environmental awareness. EPGBL is an android-based learning media that can be used in science learning, particularly for environmental pollution concepts. Quasi-experimental research with pretest and posttest group design was utilized to answer the research questions in this study. The average percentage of correct responses in the pre-test is 61.33, meanwhile, the percentage of correct responses in the post-test is 73.33. This result showed that the percentage of correct responses in the post-test is higher than in the pre-test. The results showed that EPGBL can improve students' conceptual understanding of environmental pollution concept. The average score of the students' environmental awareness character is 3.98 that include in the good criteria. In conclusion, EPGBL is effective in improving students' conceptual understanding and environmental awareness.